2001
DOI: 10.1093/aje/153.12.1152
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Factors and the Risk of Prostate Cancer

Abstract: A population-based case-control study of prostate cancer was performed in King County, Washington, in White men and Black men aged 40-64 years, between 1993 and 1996. Incident prostate cancer cases (n = 753) were identified from the Seattle-Puget Sound Surveillance, Epidemiology, and End Results (SEER) cancer registry. Controls (n = 703) were identified through random digit dialing and were frequency matched to cases on age. Sexual behavior, medical history, and other potential prostate cancer risk factors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 20 publications
8
91
1
Order By: Relevance
“…Our overall null study finding for clinical prostatitis is consistent with findings from eight previous case-control studies of clinical prostatitis and prostate cancer (7,12,15,19,(29)(30)(31)(32) but differs from those from an additional nine casecontrol studies and meta-analysis results (3,8,9,13,17,22,23,28). One methodologic concern for positive studies is detection bias, whereby men with a history of prostatitis may be followed more closely for prostate cancer than men without such a history, due to ongoing investigations for chronic prostatitis or closer medical contact following a diagnosis of prostatitis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our overall null study finding for clinical prostatitis is consistent with findings from eight previous case-control studies of clinical prostatitis and prostate cancer (7,12,15,19,(29)(30)(31)(32) but differs from those from an additional nine casecontrol studies and meta-analysis results (3,8,9,13,17,22,23,28). One methodologic concern for positive studies is detection bias, whereby men with a history of prostatitis may be followed more closely for prostate cancer than men without such a history, due to ongoing investigations for chronic prostatitis or closer medical contact following a diagnosis of prostatitis.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, no nationally representative estimates of the cumulative incidence of gonorrhea exist. Our null finding for gonorrhea is consistent with the results from eight previous case-control studies (12)(13)(14)(15)(16)(17)(18)(19) but differs from those from an additional six case-control studies and meta-analysis findings (2,7,11,(20)(21)(22)(23). Profound nondifferential misclassification of gonorrhea due to poor recall or a reluctance to report stigmatizing diseases is unlikely to explain our null result for several reasons.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In another study, Rosenblatt et al [19] found that an insignificant positive correlation existed between prostatitis and PCa if the prostatitis was diagnosed ≀ 2 years before the diagnosis of PCa was made. This finding suggests the possibility of detection bias.…”
Section: Discussionmentioning
confidence: 96%
“…44 In studies on factors such as social class, smoking, 45 alcohol consumption, 46 physical 47 and sexual activity, 48 and vasectomy, 49 the summary is that none showed a relationship with risk of prostate cancer, though some studies have shown increase in risk of prostate cancer with an increase in number of sexual partners. 50 There is an increase in odds ratio to 1.57 for prostate cancer in those who had prostatitis. 51,52 …”
Section: R O L E O F H O R M O N E S a N D O T H E R P R E -D I S P Omentioning
confidence: 99%